2016
DOI: 10.1111/1749-4877.12179
|View full text |Cite
|
Sign up to set email alerts
|

Implication of metabolomic profiles to wide thermoneutral zone in Mongolian gerbils (Meriones unguiculatus)

Abstract: Mongolian gerbils (Meriones unguiculatus) have evolved a wide thermoneutral zone (26.5-38.9 °C) and high upper critical temperature, and appear to have a high tolerance for heat exposure. Here, we use a metabolomic approach to measure global metabolite profiles for gerbils between lower (27 °C) and upper critical temperatures (38 °C) to investigate the role of metabolomic characterization in maintaining basal metabolic rates within a wide thermoneutral zone. We found that in serum and liver, 14 and 19 metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In previous studies, heat stress led to upregulation of the TCA cycle, which increased levels of TCA cycle intermediates, such as citric acid, cis-aconitic acid, αketoglutaric acid, succinic acid, fumaric acid, and malic acid. 38,43 In the present study, we found that serum and urine levels of citric acid, aconitic acid, and fumaric acid were significantly higher in the SXC group in comparison with the JMY and XHC groups. Moreover, levels of citric acid, aconitic acid, and succinic acid were significantly higher in the XHC group in comparison with the JMY group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In previous studies, heat stress led to upregulation of the TCA cycle, which increased levels of TCA cycle intermediates, such as citric acid, cis-aconitic acid, αketoglutaric acid, succinic acid, fumaric acid, and malic acid. 38,43 In the present study, we found that serum and urine levels of citric acid, aconitic acid, and fumaric acid were significantly higher in the SXC group in comparison with the JMY and XHC groups. Moreover, levels of citric acid, aconitic acid, and succinic acid were significantly higher in the XHC group in comparison with the JMY group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the intermediates α-ketoglutaric acid, fumaric acid and succinic acid of the aerobic respiration-related TCA cycle were increased in plasma from animals kept at a high ambient temperature (Shi and Wang, 2016;Nonaka et al, 2018). Succinic acid can induce higher frequencies of helper T cells by amplifying the antigen presentation of monocytes through succinate receptor 1, but failed to activate T cells by itself (Rubic et al, 2008;Saraiva et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, mineral supplementation did not affect the metabolic intermediates of glycolysis in Holstein steers, which might have caused breed-specific metabolic adaptation. HS upregulates the TCA cycle, leading to higher levels of metabolic intermediates, such as citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, and malic acid [ 13 , 70 ]. In this study, decreasing patterns of succinic acid and malic acid, along with increased mineral supplementation, were observed in both breeds.…”
Section: Discussionmentioning
confidence: 99%